Multiple Adhesive Phenotypes Linked to Rosetting Binding of Erythrocytes in Plasmodium falciparum Malaria - Fernandez, Victor (American Society for Microbiology, 1998)
The cerebral form of severe malaria is associated with excessive intravascular sequestration of Plasmodium falciparum-infected erythrocytes (PRBC). Retention and accumulation of PRBC may lead to occlusion of brain microvessels and direct the triggering of acute pathologic changes. Here we report that by selection, cloning, and subcloning, we have identified rare P. falciparum parasites expressing a pan-adhesive phenotype linked to erythrocyte rosetting, a previously identified correlate of cerebral malaria. Rosetting PRBC not only bound uninfected erythrocytes but also formed autoagglutinates, adhered to endothelial cells, and bound to CD36, immunoglobulins, and the blood group A antigen. The linkage of rosetting, autoagglutination, and cytoadherence involved the coexpression on a single PRBC of ligands with multiple specificities and the binding to two or more receptors on erythrocytes and to at least two other cell adhesion molecules, including a new endothelial cell receptor for P. falciparum-infected erythrocytes. Limited proteolysis that differentially cleaved the rosetting ligand PfEMP1 from the PRBC surface abrogated all the binding phenotypes of these parasites, implicating the variant antigen PfEMP1 as a carrier of multiple ligand specificities. The results encourage the further study of pan-adhesion as a potentially important parasite phenotype in the pathogenesis of severe P. falciparum malaria.